A solution at the doorsteps: Improved biofertilizer enhances soil fertility and yield of Chili ( Capsicum an-nuumL.) in Bhutan - Sonam Tashi; Kesang Wangchuk; Erica Udas; Sonam Gaki; Kamal Aryal (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Two field experiments were conducted to evaluate the effects of locally prepared biofertilizers (Jholmal 1 and Jholmal 2) on soil properties and chili yield (Capsicum annuum L.).Method The experimental site was in west-central Bhutan. The experiments were Randomized Complete Block Designs (RCBD) consisting of three treatments (cattle dung/ urine: Jholmal 1, cattle urine: Jholmal 2, and Control), and each treatment was replicated four times. The individual plot size of each treatment was 1 m × 3 m in total the experiment occupied a total area of 36 m2. The effects of biofertilizers on soil properties and chili yield were compared before and after application.Results Overall soil pH was within the suitable range (pH 6-7) for chili cultivation, although soil pH declined significantly in Jhomal 2 and control treatments. The soil C:N ratio increased significantly in all plots after application. Plots receiving Jholmal 2 showed the highest increase in the C:N ratio (2.30%; p<0.01) after the application.  Available soil P increased after the application and was recorded highest (21.02 mg/kg; p<0.05) in plots amended with Jholmal 1. Exchangeable K declined significantly in all treatments after the application and the decline was highest (56.00 mg/kg; p<0.05) in the plots amended with Jholmal 1. The plots amended with Jholmal 1 also gave the highest chili yield in both experiments (≈13 t/ha in experiment I and ≈15 t/ha in experiment II).Conclusion Jholmal 1 has better effects on soil fertility and chili yield and could be a prospective organic biofertilizer to use in organic farms in Bhutan.